Indeterminate cell histiocytosis successfully treated with phototherapy - Maria Claudia Nogueira Zerbini; Mirian Nacagami Sotto; Fernando Peixoto Ferraz de Campos; Andre Neder Ramires Abdo; Juliana Pereira; José Antônio Sanches Junior; Jade Cury Martins (University of São Paulo, 2016)
First described in 1985, intermediate cell histiocytosis is a rare disorder of the cutaneous dendritic cell group with a varied clinical presentation and evolution. The pathologic substrate is constituted by the proliferation of indeterminate cells (ICs) that are immunophenotypically characterized by the positivity of CD1a, CD68, and faint/focal S100, plus the negativity for CD207 (langerin). The authors present the case of a healthy elderly woman who presented generalized dome-shaped reddish cutaneous nodules over her trunk, neck, face, and extremities over a period of 18 months. A laboratory and imaging work-up ruled out internal involvement. The skin biopsy was consistent with IC histiocytosis. The patient was treated with narrowband ultraviolet B phototherapy, which resulted in an excellent short-term outcome